Protective effect of Schizonepeta tenuifolia Briq. ethanolic extract against UVB-induced skin aging and photodamage in hairless mice - Gu, Min Ji; Lee, Hee-Weon; Yoo, Guijae; Kim, Donghwan; Choi, In-Wook; Kim, Yoonsook; Ha, Sang Keun (Frontiers in Pharmacology, 2023)
The purpose of this study was to illuminate the mechanism by which Schizonepeta tenuifolia Briq. (ST) ethanolic extract prevents skin photoaging in HR-1 hairless mice (HR-1). The ST ethanolic extract alleviated wrinkle formation, epidermal skin thickness, and collagen degradation in skin tissues of ultraviolet B (UVB)-irradiated HR-1 mice. Expression of matrix metalloproteinases (a wrinkle-related marker) was reduced, and tissue inhibitor of metalloproteinase 1 expression was upregulated following application of ST ethanolic extract. Furthermore, skin dehydration and levels of hyaluronidase-1 and -2 (enzymes that break hyaluronic acid) were decreased. Moreover, protein expression of hyaluronan synthases (markers of skin hydration) and hyaluronic acid levels increased following ST ethanolic extract treatment in UVB-induced photoaging HR-1 mice. In addition, the phosphorylation of mitogen-activated protein kinases (MAPKs), including p38, extracellular signal-regulated kinase, and Jun N-terminal kinase was suppressed, and expression of nuclear factor-kappa was reduced. Treatment with ST ethanolic extract also reduced advanced glycation end product (AGE) accumulation and expression of the receptor for AGE (RAGE) in skin tissue. These results suggest that ST ethanolic extract moderates skin damage caused by UV irradiation by regulating the expression of wrinkle- and hydration-related proteins, MAPKs, and RAGE.